KETERKAITAN MODAL INTELEKTUAL, STRATEGI DIVERSIFIKASI, KEPUTUSAN PENDANAAN DAN STRUKTUR KEPEMILIKAN DENGAN KINERJA KEUANGAN PADA PERBANKAN DAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN PERIODE 2017-2020 - Darmanto; Yenni Maria Sridarta; Etheldreda Prabandasari Bria (STIE St. Pignatelli Surakarta, 2022)
This study aims to determine the effect of Ownership Structure, Diversification Strategy, Intellectual Capital, and Funding Decisions on the Company's Financial Performance. The independent variables in this research are Ownership Structure, Diversification Strategy, Intellectual Capital, and Funding Decisions. Meanwhile, the Depanden variable in this study is the Company's Financial Performance.The population in this study are financial and insurance companies in the financial sector listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sample used was 40 companies using purposive sampling method. This research uses multiple linear regression analysis method.The results of hypothesis testing show that Managerial Ownership has a positive effect on financial performance, Institutional ownership has a positive effect on financial performance. Public Ownership has a positive effect on financial performance. Diversification strategy has a positive effect on financial performance,Intellectual Capital has a positive effect on financial performance., Funding decisions have a positive effect on financial performance.